Prospective evaluation of the presence, profile and evolution of asymptomatic cardiovascular disease in treatment naïve, HIV infected patients using cardiac magnetic resonance imaging after initiation on antiretroviral therapy - Robbertse, Pieter-Paul Strauss (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.